Beyond Safety Accountability - Geller, E. Scott (Government Institutes, 2001)
Written in an easy-to-read conversational tone, Beyond Safety Accountability explains how to develop an organizational culture that encourages people to be accountable for their work practices and to embrace a higher sense of personal responsibility. The author begins by thoroughly explaining the difference between safety accountability and safety responsibility. He then examines the need of organizations to improve safety performance, discusses why such performance improvement can be achieved through a continuous safety process, as distinguished from a safety program, and provides the practical tools you can use to build personal responsibility in your workplace.